Rancang Bangun Sistem Pendukung Keputusan Seleksi Tenaga Kerja Dengan Metode Profile Matching (Studi Kasus Pt. Adhi Karya (Persero), Tbk Divisi Konstruksi VII) - I Yoman Ega Beerawa; Teguh Sutanto; Tegar H. Susilo (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2012)
The success of a company of course could not be separated from the role of labor as a human resources (HR) that run all sorts of activities for the betterment of the workplace. Therefore, HR must be maintained and be selected appropriately in order to show good performance and optimum. This applies to new labor and labor that has long worked in the career development process. In the election or selection of labor is often the polemics, because there is the possibility of a subjective assessment of a person so that the process is not running properly and the results achieved may not be suitable targets. Here we need a system that can handle the selection of an appropriate workforce with the competencies required by positions held in accordance with the criteria. The underlying reason that the construction of a decision support system selection this workforce. Expected that this system can assist the managers in analyzing the labor office in accordance with certain criteria. System programs to be created will help overcome the problems that occur in the company. This system can perform data maintenance processes, as well as profile matching the selection process itself. The system to be produced will be more to help decision makers and not replace them. It is hoped this system can also improve the effectiveness and efficiency of decision-making process itself. Keywords : decision support systems, selection, profile matching